International overview of sea turtle fibropapillomatosis: a survey of expert opinions and trends - Whilde, Jenny; Mashkour, Narges; Koda, Samantha A.; Eastman, Catherine B.; Thompson, Drew; Burkhalter, Brooke; Frandsen, Hilary R.; Page, Annie; Blackburn, Nicholas B.; Jones, Karina; Ariel, Ellen; Dupont, Sophie M.; et al. (Frontiers in Cell and Developmental Biology, 2024)
Marine environments offer a wealth of opportunities to improve understanding and treatment options for cancers, through insights into a range of fields from drug discovery to mechanistic insights. By applying One Health principles the knowledge obtained can benefit both human and animal populations, including marine species suffering from cancer. One such species is green sea turtles (Chelonia mydas), which are under threat from fibropapillomatosis (FP), an epizootic tumor disease (animal epidemic) that continues to spread and increase in prevalence globally. In order to effectively address this epizootic, a more thorough understanding is required of the prevalence of the disease and the approaches to treating afflicted turtles. To identify knowledge gaps and assess future needs, we conducted a survey of sea turtle FP experts. The survey consisted of 47 questions designed to assess general perceptions of FP, the areas where more information is needed, local FP trends, the disease status, and mitigation needs, and was voluntarily completed by 44 experts across a broad geographic range. Over 70% of respondents both recognized FP as a cancerous panzootic disease, and reported that FP is increasing in prevalence. They report several factors contributing to this increase. Nearly all of the respondents reported that FP research, patient treatment and rehabilitation required more funding in their area, and reported inadequate facilities and capacity for dealing with FP patients. Treatment approaches varied: just over 70% of the medical experts that responded surgically remove FP tumors, either using laser or scalpel. Just under half of respondents use anti-cancer drugs in their treatment of FP. Internal tumors were reported as justification for euthanasia by 61.5% of respondents, and 30.8% reported severe external tumors to be sufficient grounds for euthanasia. Most medical respondents (93.3%) routinely perform necropsy on deceased or euthanized FP-afflicted turtles. Over 80% of respondents considered large-scale multidisciplinary collaboration 'extremely important' for advancing the field of FP research. The survey responses provide a valuable insight into the current status of FP in sea turtles, FP treatment, rehabilitation and research, and help to identify critical FP-related areas most in need of attention.